1
$\begingroup$

I have the following proposition:

$$p\to\neg q, q\vdash \neg p$$

Using the following formulas on propositions is easy enough:

$$\frac{\psi \qquad \psi\to\varphi}{\varphi}\quad \to_e$$

$$\frac{\psi\to\varphi \qquad \neg\varphi}{\neg\psi}\quad \to_{\rm MT}$$

However the statement $p\to\neg q$ above has a negation on $q$, so I'm not sure how to apply these formulas. Can someone help me out?

$\endgroup$
  • 1
    $\begingroup$ I'm having trouble parsing your notation. Is it perhaps intended to be $\dfrac{\psi\quad \psi\to\phi}{\phi}\ \to_e$ and $\dfrac{\phi \to \phi\quad \neg \phi}{\neg \psi} \ \to_{MT}$? $\endgroup$ – Lord_Farin Jan 28 '15 at 20:39
  • $\begingroup$ @Lord_Farin yes thats it, i couldn't figure out how to write it that way. $\endgroup$ – Bolboa Jan 28 '15 at 20:39
1
$\begingroup$

1) $p → ¬q$ --- premise

2) $q$ --- premise

3) $p$ --- assumed [a]

4) $\lnot q$ --- from 1) and 2) by $\rightarrow$-elimination

5) $\bot$ --- from 3) and 4) by $\rightarrow$-introduction

6) $\lnot p$ --- from 2) and 5) by $\lnot$-introduction, discharging assumption [a].

Thus, from 1), 2) and 8) we have :

$p → ¬q, q \vdash \lnot p$.


If you have the MT rule available, you have simply to apply it :

1) $p \rightarrow \lnot q$ --- premise

2) $q$ --- premise

3) $\lnot \lnot q$ --- from 2) by Double Negation

4) $\lnot p$ --- from 1) and 3) by MT.

$\endgroup$
  • $\begingroup$ I do like this answer, but can it also be done without the use of assumption? If not, this will do. $\endgroup$ – Bolboa Jan 28 '15 at 20:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.